Guest Editorial Special Issue of Best Conference Papers in Ieee Conf. in Latin America 2017 - Acosta-Barbosa, K (IEEE Computer Society, 2018)
This is a special issue of IEEE Latin America Transactions for 2018 that presents the trends of emerging technologies and the best research work in our countries. This volume presents trends in emerging technologies, and the best extended conferences in Latin America that show how Latin American countries work towards solving the main problems that our countries have. © 2018 IEEE.